DEVELOPMENT OF INTEGRATED SCIENCE E-MODULES THROUGH PROBLEM-BASED LEARNING TO IMPROVE CRITICAL THINKING ABILITY AND STUDENTS' LEARNING OUTCOMES ON VIBRATION AND WAVES - Sakka Irawan; Jonner Nainggolan; Virman Virman (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
This study aims to determine the feasibility of developing an integrated science e-module through problem-based learning in improving critical thinking skills and student learning outcomes on vibration and wave material. The research method used was Research and Development. The research sample was class VIII Junior High School 2 Jayapura with a total of 30 students. The results showed that the integrated science e-module for vibration and wave material was very feasible to be used as a teaching material with an average validator rating of 90.89%. The use of integrated science e-modules can improve critical thinking skills and increase student learning outcomes by 0.57 in the medium category and 0.74 in the high category.